Does cardiovascular preparticipation screening cause psychological distress in athletes? A systematic review. (23rd November 2022) - Hill, Braeden; Grubic, Nicholas; Williamson, Matthew; Phelan, Dermot M; Baggish, Aaron L; Dorian, Paul; Drezner, Jonathan A; Johri, Amer M
Abstract : Objective: To evaluate the psychological implications of cardiovascular preparticipation screening (PPS) in athletes. Design: Systematic review. Data sources: MEDLINE, EMBASE, PubMed, CINAHL, SPORTDiscus, APA PsycInfo, Cochrane Library and grey literature sources. Study eligibility criteria: Observational and experimental studies assessing a population of athletes who participated in a cardiovascular PPS protocol, where psychological outcomes before, during and/or after PPS were reported. Methods: Results of included studies were synthesised by consolidating similar study-reported measures for key psychological outcomes before, during and/or after screening. Summary measures (medians, ranges) were computed across studies for each psychological outcome. Results: A total of eight studies were included in this review (median sample size: 479). Study cohorts consisted of high school, collegiate, professional and recreational athletes (medians: 59% male, 20.5 years). Most athletes reported positive reactions to screening and would recommend it to others (range 88%–100%, five studies). Increased psychological distress was mainly reported among athletes detected with pathological cardiac conditions and true-positive screening results. In comparison, athletes with false-positive screening results still reported an increased feeling of safety while participating in sport and were satisfied with PPS. A universal conclusion across all studies was that most athletes did not experience psychological distress before, during or after PPS, regardless of the screening modality used or accuracy of results. Conclusion: Psychological distress associated with PPS in athletes is rare and limited to athletes with true-positive findings. To mitigate downstream consequences in athletes who experience psychological distress, appropriate interventions and resources should be accessible prior to the screening procedure. PROSPERO registration number: CRD42021272887.